Applied learning innovation: Evaluating the effects of self-efficacy and Project-based blended learning on computational thinking skills - Anggrasari, Liya Atika; Degeng, I Nyoman Sudana; Kuswandi, Dedi; Praherdhiono, Henri; Hadi, Fida Rahmantika (Edelweiss Applied Science and Technology, 2025)
In today’s digital age, it is crucial to equip future elementary teachers with computational thinking skills to address the educational needs of the 21st century. This research examines how project-based blended learning and self-efficacy influence students’ computational thinking abilities within the realm of primary teacher education. A quasi-experimental 2×2 factorial design was utilized, involving 74 undergraduate students from Universitas PGRI Madiun, Indonesia. Participants were divided into either a project-based blended learning group or a non-blended project-based learning group and further classified based on high or low self-efficacy levels. Data collection involved validated self-efficacy questionnaires and computational thinking assessments, with analysis conducted using two-way ANOVA. The results indicate a significant main effect of project-based blended learning (p = 0.02) and self-efficacy (p = 0.00) on computational thinking skills, while no significant interaction was found between the two variables (p = 0.431). These findings underscore the individual effectiveness of blended, project-based methods and learner confidence in enhancing computational thinking. The study adds to the growing body of evidence supporting technology-integrated teaching methods in teacher education programs and provides practical insights for curriculum developers aiming to cultivate computational skills in future educators.